2009
DOI: 10.1021/jp900541b
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Excited-State Dynamics of Kynurenine, a UV Filter of the Human Eye

Abstract: The excited-state dynamics of kynurenine (KN) has been examined in various solvents by femtosecondresolved optical spectroscopy. The lifetime of the S 1 state of KN amounts to 30 ps in aqueous solutions, increases by more than 1 order of magnitude in alcohols, and exceeds 1 ns in aprotic solvents such as DMSO and DMF, internal conversion (IC) being shown to be the main deactivation channel. The IC rate constant is pH independent but increases with temperature with an activation energy of about 7 kJ/mol in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
84
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 71 publications
13
84
0
Order By: Relevance
“…27,28 It has also been demonstrated that the chemical denaturation of the protein allows more bulk type water in the protein cavity, revealing faster time constants in the solvation dynamics. 27,28 A systematic study on the spectroscopy and dynamics of kynurenine in different solvents has been presented by Vauthey et al 16 The usefulness of the probe (kynurenine) as a solvation reporter has also been established. 16 The main excited-state deactivation channel of the probe depends on the interaction of the solvent molecules through hydrogen-bonding ability.…”
Section: Resultsmentioning
confidence: 99%
“…27,28 It has also been demonstrated that the chemical denaturation of the protein allows more bulk type water in the protein cavity, revealing faster time constants in the solvation dynamics. 27,28 A systematic study on the spectroscopy and dynamics of kynurenine in different solvents has been presented by Vauthey et al 16 The usefulness of the probe (kynurenine) as a solvation reporter has also been established. 16 The main excited-state deactivation channel of the probe depends on the interaction of the solvent molecules through hydrogen-bonding ability.…”
Section: Resultsmentioning
confidence: 99%
“…The early excited-state dynamics of KNY is similar to that of KN. 1 It has been shown that excitation of KN and other UV filters results in a charge transfer from the amino to the carbonyl group; 35 very likely that the same charge transfer occurs during the KNY excitation, which is supported by a large Stokes shift of the fluorescence band relative to the absorption spectrum (Fig. 1).…”
Section: Photophysics and Photochemistry Of Knymentioning
confidence: 93%
“…Most likely, the IC mechanism of KNY is similar to that of KN and other UV filters, and includes transformation of the absorbed light energy into heat via hydrogen bond vibrations. 1,2,35 Photolysis of KNY in aqueous solution results in the formation of two intermediates, observed by nanosecond flashphotolysis, namely the KNY triplet state and the species which was attributed to the KNY enol form in the ground state, and of two products detected in the irradiated samples by HPLC, i.e. 4HQN and DHQN.…”
Section: Photophysics and Photochemistry Of Knymentioning
confidence: 99%
See 1 more Smart Citation
“…13,[32][33][34][35][36][37][38][39] This process is enabled by the nitro groups of EB that are good hydrogen-bond acceptors. [24][25][26]40,41 In order to further confirm this hypothesis, TA measurements were carried out in perdeuterated water.…”
Section: Articlementioning
confidence: 99%